Revisiting sustainable financial behavior: The distinct roles of financial well-being, mental health, and consumption behavior - Abelia Fatimah Handayani; Hadi Ismanto; Rabeatul Husna Abdull Rahman (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2026)
This study investigates the influence of financial well-being and mental health on employee financial behavior, both directly and indirectly through consumption behavior, within emerging economies. Although prior studies have widely examined financial literacy and economic determinants of financial behavior, limited attention has been given to the combined role of psychological well-being and consumption patterns in shaping sustainable financial decisions. In addition, the mediating role of consumption behavior in explaining the relationship between financial well-being, mental health, and financial behavior remains underexplored. Using a quantitative approach, data were collected from 140 private-sector employees in Indonesia and analyzed using PLS–SEM. The findings reveal that financial well-being, mental health, and consumption behavior significantly and positively affect employee financial behavior. Furthermore, financial well-being significantly influences consumption behavior, which mediates the relationship between financial well-being and financial behavior. However, consumption behavior does not mediate the relationship between mental health and financial behavior, highlighting that psychological stability may directly strengthen employees’ capacity for responsible financial planning and long-term financial management. This study contributes to the behavioral finance and strategic management literature by combining psychological and financial factors in employee financial decision-making and extending the Theory of Planned Behavior by including mental health in financial behavior.